Pancasila dan Hukum Internasional : Kajian tentang Prinsip Kedaulatan dan Hak Asasi Manusia dalam Perspektif Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Aliffah Putri Faradina; Amelia Septiana Putri; Rahma Widianingrum (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Pancasila, as the foundation of the Republic of Indonesia, is an ideology that influences various aspects of the life of the nation and state, including in the context of international law. This study aims to explore the interaction between the principles of Pancasila and the norms of international law, particularly in relation to state sovereignty and human rights. The main focus of this study is how the principles of sovereignty and human rights, which are pillars in international law, are integrated and translated in the context of Pancasila, and how this affects Indonesia's position in the global arena. This research uses a qualitative approach with a documentary study method, collecting data from books, scientific journal articles, and recent legal documents. It analyzes the application of Pancasila principles in Indonesian national law and its impact on international obligations, particularly in terms of human rights protection. The study also examines the challenges faced by Indonesia in harmonizing the principles of national sovereignty with its commitment to international human rights standards. The results show that the principles of Pancasila, such as Social Justice and Indonesian Unity, provide a strong foundation for safeguarding state sovereignty. However, there are significant challenges in integrating international human rights principles, particularly in the context of protecting minority rights and upholding global human rights standards. The research also identifies Indonesia's efforts in balancing national interests with international obligations through foreign policy and diplomacy. The implications of this research suggest the need for a more holistic and strategic approach to address the tension between state sovereignty and human rights in the global context.